Pembelajaran Sholat Jenazah sebagai Upaya Penanaman Kesadaran Fardhu Kifayah Peserta Didik: Program KKN Mahasiswa STAI Solok Nan Indah Di Jorong Baduih, Nagari Simawang Tahun 2026 - Nurhayati; Bintang Ramadhan; Dina Dahliana; Esti Nur Qorimah (Journal of Social Empowerment, 2026)
This article reports the implementation of a Community Service Learning (Kuliah Kerja Nyata/KKN) program conducted by students of STAI Solok Nan Indah in Jorong Baduih, Nagari Simawang, Tanah Datar Regency, West Sumatra, in 2026. The program employed a Participatory Action Research (PAR) approach to enhance elementary school students' knowledge and practical skills in performing sholat jenazah (Islamic funeral prayer), a fardhu kifayah (collective religious obligation). The intervention consisted of two sequential sessions implemented as part of the Ramadhan Boarding School program at SDN 19 Simawang. The first session, held on March 6, focused on theoretical instruction covering the significance, pillars, procedures, and intentions of sholat jenazah. The second session, conducted on March 7, provided guided practical demonstrations and hands-on practice. Program effectiveness was evaluated through assessments of both theoretical understanding and practical performance. The results showed an average score of 82.8 (on a 0–100 scale) for theoretical knowledge and 84.5 for practical skills, with both outcomes categorized as Berkembang Sesuai Harapan (Developing as Expected). These findings indicate that a structured PAR-based learning model integrating theoretical instruction with supervised practice effectively strengthens students' competence in performing sholat jenazah. The study demonstrates the potential of community-engaged service-learning programs to reinforce Islamic religious education by promoting both conceptual understanding and practical religious competence in school settings.